Efficacy and safety of respiratory syncytial virus vaccination during pregnancy to prevent lower respiratory tract illness in newborns and infants: a systematic review and meta-analysis of randomized controlled trials - Ma, Juan; Chen, Long; Tang, ShiFang; Shi, Yuan (Frontiers in Pediatrics, 2024)
To evaluate the effectiveness and safety of respiratory syncytial virus (RSV) vaccination during pregnancy in preventing lower respiratory tract infection (LRTI) in infants and neonates, we conducted a systematic search of randomized controlled trials (RCTs) in five databases (PubMed, Embase and Cochrane Library, Web of Science, Cochrane Center Register of Controlled trial) until 1 May 2023. We performed a meta-analysis of the eligible trials using RevMan5.4.1 software. Our analysis included six articles and five RCTs. The meta-analysis revealed significant differences in the incidences of LRTI [risk ratio (RR): 0.64; 95% confidence interval (CI): 0.43, 0.96; p = 0.03)] and severe LRTI (RR: 0.37; 95% CI: 0.18, 0.79; p = 0.01) between the vaccine group and the placebo group for newborns and infants. These differences were observed at 90, 120, and 150 days after birth (p = 0.003, p = 0.05, p = 0.02, p = 0.03, p = 0.009, p = 0.05). At 180 days after birth, there was a significant difference observed in the incidence of LRTI between the two groups (RR: 0.43; 95% CI: 0.21, 0.90; p = 0.02). The safety results showed a significant difference in the incidence of common adverse events between the two groups (RR: 1.08; 95% CI: 1.04, 1.12; p < 0.0001). However, there was no significant difference observed in the incidence of serious adverse events (RR: 1.05; 95% CI: 0.97, 1.15; p = 0.23), common and serious adverse events (RR: 1.02; 95% CI: 0.96, 1.10; p = 0.23), or common and serious adverse events among pregnant women and newborns and infants (RR: 0.98; 95% CI: 0.93, 1.04; p = 0.52). In conclusion, maternal RSV vaccination is an effective and safe immunization strategy for preventing LRTI in postpartum infants, with greater efficacy observed within the first 150 days after birth.